High-Performance Work Systems And Firm Performance: Moderating Effects Of Organizational Communication - Lee, Gyeonghwan; Lee, Myeongju; Sohn, Yoonhwan (Journal of Applied Business Research, 2017)
This study examines the relationship between high-performance work systems (HPWS) and organizational performance and how the relationship differs by type of communication within organizations. Using data on publicly traded manufacturing firms in Korea from the Human Capital Corporate Panel survey, we find that HPWS are positively related to organizational performance, and importantly, this relationship varies by the level of vertical and horizontal communication. The positive effect of HPWS on organizational performance is more apparent when vertical and horizontal communications are relatively high. These results emphasize the role of internal communication as an important organizational context for the implementation of HPWS.
Keywords: High-Performance Work System; Organizational Communication; Vertical Communication; Horizontal Communication